299. Tolerance and Serum Concentration of Cefepime Used Subcutaneously (SC) in the Management of Bone and Joint Infections. (26th November 2018) - Assaf, Addy; Robineau, Olivier; Titecat, Marie; Allorge, Delphine; Hennart, Benjamin; Loyez, Caroline; Migaud, Henri; Senneville, Eric
Abstract: Background: Cefepime is a cephalosporin active against most Gram positive and negative bacteria and is used in the management of bone and joint infections (BJIs). Intravenous (IV) perfusion is the standard route of administration. The Subcutanoeous (SC) route may present an interesting alternative in case of outpatient care or when IV perfusion is not possible. The aim of this study was to demonstrate that the SC route of administation for cefepime provides effective serum concentrations in the treatment of BJIs without route-specific side effects. Methods: Descriptive analysis of a bi-center retrospective observational study from January 2011 to February 2017 in patients with an BJI treated with cefepime SC and who had a cefepime plasma level dosage. Cefepim Cmax and Cmin were considered optimal if they were superior to five MIC. Results: Eleven patients were included with 21 dosages of cefepime SC, 12 Cmax and nine Cmin. The mean age of the patients was 58 ± 17 years and the mean body mass index was 26.6 ± 5.6. Cefepime was used for the management of infections with at least one Gram-negative bacillus (GNB) (64% of infections were plurimicrobial). Combination with at least one other antibiotic was found in 68% of cases. The median C max and C min levels were 57 mg/L (39.5–124) and 14 mg/L (0–42), respectively. C max was above five MIC for all patient and C min was above this threshold in eight (80%) patients but still well above the MIC of GNB. No local complications related to the SC administration of cefepime has been described. Conclusion: Plasma concentration during SC administration of cefepime seems to reach similar value to the IV route founded in the literature for BJI management. SC administration appears to be a well-tolerated alternative in the management of BJI. Further prospective clinical efficacy studies are needed. Disclosures: All authors: No reported disclosures.